2017
DOI: 10.1101/148726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ELMER v.2: An R/Bioconductor package to reconstruct gene regulatory networks from DNA methylation and transcriptome profiles

Abstract: Recent studies indicate that DNA methylation can be used to identify changes at transcriptional enhancers and other cis-regulatory elements in primary human samples. A systematic approach to inferring gene regulatory networks has been provided by the R/Bioconductor package ELMER (Enhancer Linking by Methylation/Expression Relationships), which first identifies DNA methylation changes in distal regulatory elements and correlates these with the expression of nearby genes to identify direct transcriptional target… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Illumina HM450 methylation data from 4 different TCGA projects, COAD-READ, ESCA, PAAD, and STAD were processed with SeSAMe[51], and the matched RNA-seq (FPKM-UQ) data were downloaded from GDC (Genomic Data Commons, https://portal.gdc.cancer.gov/) from the harmonized database (data aligned to hg38/GRCh38). Unsupervised analysis was performed using ELMER[52] for the following pair-wise comparisons: EAC primary tumors (n = 78) vs ESCC primary tumors (n = 76); EAC primary tumors (n = 78) vs EAC normal adjacent samples (n = 5), COAD-READ primary tumors (n = 389) vs colon normal adjacent samples (n = 21), PAAD primary tumors (n = 177) vs pancreas normal adjacent samples (n = 4). Because of the small number of normal adjacent samples from STAD (n=2) which also lacked RNA-seq data, we could not perform comparison for STAD primary tumors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Illumina HM450 methylation data from 4 different TCGA projects, COAD-READ, ESCA, PAAD, and STAD were processed with SeSAMe[51], and the matched RNA-seq (FPKM-UQ) data were downloaded from GDC (Genomic Data Commons, https://portal.gdc.cancer.gov/) from the harmonized database (data aligned to hg38/GRCh38). Unsupervised analysis was performed using ELMER[52] for the following pair-wise comparisons: EAC primary tumors (n = 78) vs ESCC primary tumors (n = 76); EAC primary tumors (n = 78) vs EAC normal adjacent samples (n = 5), COAD-READ primary tumors (n = 389) vs colon normal adjacent samples (n = 21), PAAD primary tumors (n = 177) vs pancreas normal adjacent samples (n = 4). Because of the small number of normal adjacent samples from STAD (n=2) which also lacked RNA-seq data, we could not perform comparison for STAD primary tumors.…”
Section: Methodsmentioning
confidence: 99%
“…Our earlier work demonstrated that this form of de-methylation could be used to identify cancer-specific enhancers which were strongly enriched for specific transcription factor binding sites (TFBSs)[14]. Recently, we have developed a novel computational algorithm, ELMER (Enhancer Linking by Methylation/Expression Relationships), to identify and exploit systematically these TFBS-associated methylation changes in cancer[17, 18]. Briefly, the approach of ELMER is to utilize TFBS methylation changes as key nodes within the larger gene regulatory network, and correlate with gene expression to infer both the upstream (master regulator TFs, MRTFs) and downstream (target genes) links for each TFBS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, using the DNA methylation data and the gene expression data the R/Bioconductor ELMER package can be used to discover functionally relevant genomic regions associated with cancer [7,8].…”
Section: Graphical User Interface Designmentioning
confidence: 99%
“…The following R/Bioconductor packages are used as back-ends for the data retrieval and analysis: TCGAbiolinks [2] which allows to search, download and prepare data from the NCI's Genomic Data Commons (GDC) data portal into an R object and perform several downstream analysis; ELMER (Enhancer Linking by Methylation/Expression Relationship) [7,8] which identifies DNA methylation changes in distal regulatory regions and correlate these signatures with the expression of nearby genes to identify transcriptional targets associated with cancer; ComplexHeatmap [9] to visualize data as oncoprint and heatmaps, pathview [10] which offers pathway based data integration and visualization; and maftools [11] to analyze, visualize and summarize MAF (Mutation Annotation Format) files.…”
Section: Infrastructurementioning
confidence: 99%